PENGUKURAN KINERJA PEMASARAN PRODUK CHICKENESIA (STUDI KASUS PADA PT. BINTANG AZKI ABADI) - Nurliani Nurliani; Nurfanizah Nurfanizah; Mais Ilsan (AGRIBIOS, 2025)
Marketing performance is the output of all efforts and marketing strategies that have been carried out by entrepreneurs. Knowing the marketing strategy and performance, will be very useful as a basis for evaluation and business development in the future. This study aims to: 1) analyzing the marketing performance of Chickenesia frozen crispy chicken products in Makassar City and 2) evaluating the marketing performance of Chickenesia frozen crispy chicken products. The approach method uses experiential learning method. Quantitative descriptive data analysis based on entrepreneurial prototypes to describe marketing performance. The results showed that the measurement of marketing performance using marketing metrics. Marketing costs in the January-March 2025 period, amounted to Rp 1,152,750, a profitability value of Rp 376,900, and the highest return on sales value in the super special package, which is 90%. The development of marketing strategies through business-to-consumer (B2C) and business-to-business (B2B) approaches has given positive results to sales turnover, because it is able to reach all consumer segments that are the target market. Entrepreneurship activities provide benefits for the development of the ability to analyze markets and competitors, soft skills development, and communication skills.